The Legal Politics Of Relocating The National Capital: An Analysis Of Law No. 21 Of 2023 From The Perspective Of Mahfud Md’s Theory Of Legal Politics - Ansori, Saiful; Maghfiroh, Siti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This article examines the close relationship between law and politics from a legal-political perspective, emphasizing Mahfud MD's thinking and its implementation in the formation of Law Number 3 of 2022 concerning the National Capital (IKN), which was later revised into Law Number 21 of 2023. This study utilizes political configuration theory and the character of legal products. This research is qualitative with a normative-juridical approach. The data sources consist of primary and secondary sources. Data collection techniques were conducted through literature review and systematic document review of primary and secondary legal sources. The data analysis technique used was normative-juridical analysis. This research demonstrates that law is inherently inseparable from political interests. The case study of the IKN Law demonstrates executive dominance and a solid political coalition, with a rapid legislative process but minimal public participation. The resulting law tends to be conservative-elitist, despite containing aspirational elements such as equitable development and sustainability. These findings confirm that law as a political product can function to legitimize strategic policies, but also leaves behind problems of participation and the potential for marginalization of society.